1981
DOI: 10.1111/j.1471-4159.1981.tb04674.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Collagen‐Tailed Acetylcholinesterase from Chick Retina: Effect of Different Extraction Procedures

Abstract: We have extracted acetylcholinesterase from young chick retinas by homogenization in different solutions combining high salt concentration, ionic and nonionic detergents, and EDTA, looking for an optimum procedure for the solubilization of collagen-tailed, asymmetric structural forms of the enzyme. High salt and EDTA seem to be the only necessary requirements for the solubilization of acetylcholinesterase as the A12 form (20S), and the presence of detergent in the homogenization medium does not significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We have previously characterized KA binding sites in chick tectal and cerebellar membranes from pharmacological and developmental standpoints [16, 17]. We have also shown that GNs, including GMP, are efficient displacers of [ 3 H]KA [8, 11].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously characterized KA binding sites in chick tectal and cerebellar membranes from pharmacological and developmental standpoints [16, 17]. We have also shown that GNs, including GMP, are efficient displacers of [ 3 H]KA [8, 11].…”
Section: Resultsmentioning
confidence: 98%
“…Results with chick KA receptors are specially illustrative in this respect [8, 10, 11]. Chick tectal or cerebellar membranes contain abundant medium/low affinity binding sites ( K d in the range of 100–300 nM) that have been analyzed in different laboratories [14, 16, 17]and, in more recent years, purified and cloned [14, 18].…”
Section: Discussionmentioning
confidence: 99%
“…They were, however, subsequently observed in the motor nerve itself [19,75,761, in various peripheral ganglia [23, 771 and, subsequently, in the central nervous system. Thus Ramirez and coworkers [78,79] clearly demonstrated the presence, in the chick visual system (i.e. in tectum and retina) of A forms displaying the same physicochemical parameters and collagenase sensitivity as the corresponding forms in chick skeletal muscle.…”
Section: Physicochemical Basis For Interaction With the Cell Surfacementioning
confidence: 99%
“…1). Thus retina differs from other chick brain regions, such as tectum and cerebellum, where only the low‐affinity site has been found [10, 25]. These receptors would be, in principle, the molecular substrate for the excitotoxic action of KA in the chick retina, already a firmly established fact [14–21, 26, 27].…”
Section: Discussionmentioning
confidence: 95%